Respekt og kompromis – en forelæsning - Rostbøll, Christian F. (Politik, 2015)
This lecture addresses the democratic signi cance of compromise. Are compromises merely an unfortunate necessity in politics because citizens and legislators cannot achieve consensus? Does a majority have demo- cratic reasons for making concessions to a minority if it can make decisions on its own? In short, is com- promise a democratic value in and of itself? e lecture concludes that there are non-pragmatic democratic reasons for making compromises, which are based on respect towards fellow citizens and legislators. Compro- mises may make decisions more democratic, but only under certain conditions. We are not obliged to make compromises with anyone. Some compromises may undermine the very ideal of compromise. Moreover, by making compromises with someone, we grant them legitimacy, and there are limits as to which political opponents we should grant legitimacy.